Evaluating Makiwara Punching Board Performance (Revista de Artes Marciales Asiáticas, 2012)
No studies quantifying the impact characteristics of makiwara boards are available in the published literature. Logically, an initial step in determining the validity of the makiwara to develop karate technique would be to assess the mechanical characteristics of various types of makiwara board designs. It was, therefore, the purpose of this study to determine the stiffness of selected tapered board and stacked board makiwara training devices using static loading techniques to assess their suitability for practitioners of different levels. When our results are viewed in terms of progression of training, it would appear that a novice would be more suited to the more compliant ash stacked design and the expert more suited to the stiffer oak tapered design.